Structure-Activity Correlations of Cu/Zno Catalysts Derived from Different Precursors as a Function of Aging - Muhamad, Ernee Noryana (2006)
Structural modifications of Cu/ZnO catalysts for methanol steam reforming (MSR) have been investigated as a function of precipitate aging in the catalyst preparation process. Freshly precipitated Cu,Zn-hydroxycarbonate precursor (HC) and Cu,Zn-hydroxynitrate precursor (HN) were aged in their mother liquor for 120 min followed by washing, drying, calcination and reduction. The characteristics of the precursors before and after aging were determined by means of TG/MS, XRD, and SEM. Generally, more pronounced aging effect was observed for HC precursor (reference catalyst) while no significant effect of aging was observed for HN precursor. In order to determine the microstructural changes as a function of aging, the bulk structure of the Cu/ZnO catalysts was investigated by in-situ XRD, XAS, 63Cu NMR and HRTEM. The observed increase in the activity of the catalysts prepared by HC aging iv coincides with a decrease in copper crystallite size (i.e. an increase in Cu surface area) and an increase in the microstrain in the copper clusters presumably because of the improved interface between Cu and ZnO in comparison to the HN prepared catalysts. Aging of the HN precursors results in large, separated and less strained Cu and ZnO particle with an inferior catalytic activity compared to aging of the HC precursors. An increase in catalytic activity of HN and HC was observed significantly after temporary addition of oxygen was done to the feed mixture. The higher catalytic activity does not correlate with an increase in copper surface area, microstrain or oxygen in copper cluster (Cu-EXAFS), but due to slight changes of the catalyst in the medium range order of Cu and ZnO in XAS analysis. Furthermore, the HRTEM and 63Cu NMR investigations revealed that the copper particles get more sintered resulting in less interfacial contact of Cu to ZnO as was observed after the O2 pulse. Based on these comparative investigations, a structural model of the active catalyst as a function of aging was proposed for the HN preparative route